The toll of unemployment in axial spondyloarthropathy: high prevalence and negative impact on outcomes captured in a national registry. (4th July 2022) - Maguire, S; Wilson, F; Gallagher, P; O'Shea, F
Abstract : Objective: Axial spondyloarthropathy (axSpA) is an inflammatory arthritis of the axial skeleton. Persistent disease activity can result in significant disability and affect the ability to maintain employment. This study aimed to determine the prevalence of unemployment in axSpA and the impact on patient outcomes. Method: Data from the Ankylosing Spondylitis Registry of Ireland (ASRI) were cleaned, and information on employment, demographics, and disease characteristics was extracted. Patients were analysed on the basis of employment and categorized as employed or unemployed. Results: Of the 759 participants included in the analysis, 23.5% (178) were unemployed, higher than national averages of 6.2–13.1% during the study period. Unemployed participants reported significantly worse Bath Ankylosing Spondylitis Disease Activity Index (BASDAI; 5.1 vs 3.6), Metrology Index (BASMI; 4.8 vs 3.4), Functional Index (BASFI; 5.2 vs 3.0), Health Assessment Questionnaire (HAQ; 0.82 vs 0.40), and Ankylosing Spondylitis Quality of Life (ASQoL; 9.4 vs 5.4) scores compared to employed (all p < 0.01). Male gender (odds ratio, 95% confidence interval: 2.65, 1.46–4.83), worse BASMI (1.16, 1.02–1.33), and worse HAQ scores (2.18, 1.13–4.19) were significantly associated with unemployment. Conclusion: The prevalence of unemployment in axSpA patients is higher than in the general population, and is associated with worse quality of life, poorer levels of function, and higher levels of disease activity. Predictors of unemployment in axSpA were male gender, worse spinal mobility, and poorer level of function. Recognition of patients at risk of unemployment will improve opportunities for intervention and maintain participation in the workforce.